Synthesis of 5-arylazothiazoles, pyridines and thieno[2,3-b]pyridines derivatives containing 1,2,3-triazole moiety - Abdelhamid, Abdou Osman; Abdel-Riheem, Nadia Abdelhamid; El-Idreesy, Tamer Tawhid; Rashdan, Huda Refat Mahmoud (European Journal of Chemistry, 2012)
1-(2-(4,5-dihydro-3-(5-methyl-1-phenyl-1H-1,2,3-triazol-4-yl)-5-phenylpyrazol-1-yl)-4-subs-tituted-thiazol-5-yl)-2-phenyldiazene (4) and substituted pyridines (5-12) were synthesized via reaction of 1-(5-methyl-1-phenyl-1H-1,2,3-triazol-4-yl)-3-phenylprop-2-en-1-one with hydrazonoyl halides and active methylene compounds. Also, thieno[2,3-b]pyridines (14a-e) were prepared through reactions of 2-mercapto-6-(5-methyl-1-phenyl-1H-1,2,3-triazol-4-yl)-4-phenyl-pyridine-3-carbonitrile with halo ester and halo ketones, respectively. The newly synthesized derivetived were elucidated by elemental analysis, spectral data and alternative synthetic routes wherever possobile.